2015
DOI: 10.1007/s40556-015-0052-0
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Progesterone in Asymptomatic Women with Short Cervical Length on Ultrasound: is it Beneficial?

Abstract: The aim of the present study was to determine the efficacy of vaginal progesterone in asymptomatic women with a sonographic short cervix (B25 mm) at 18-24 weeks of gestation in reducing the risk of preterm birth. It was a prospective observational study carried out on 60 pregnant women attending the antenatal clinic in tertiary health institute between 18 and 24 weeks of gestation with ultrasonographically-measured short cervix. The women with cervical length B25 mm were alternately divided into two groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
3
1
0
Order By: Relevance
“…Results in the birth weight of less than 2.5 kg have been found to be statistically significant in the present study (p = 0.033). Similar results were seen in study by Romero et al 15 However non significant results were seen in other studies done by Fonseca et al, Hassan et al, and Anjali et al [12][13][14] In terms of neonatal sepsis and requirement of ventilator the results have been found to be statistically significant in present study similar to the study by Fonseca et al with their results also found to be statistically significant. 6 In terms of admission to NICU, similar results were seen in other two studies mentioned by Fonseca et al, and Romero et al, with their results also found to be statistically significant (p = 0.05 and p = 0.003 respectively).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Results in the birth weight of less than 2.5 kg have been found to be statistically significant in the present study (p = 0.033). Similar results were seen in study by Romero et al 15 However non significant results were seen in other studies done by Fonseca et al, Hassan et al, and Anjali et al [12][13][14] In terms of neonatal sepsis and requirement of ventilator the results have been found to be statistically significant in present study similar to the study by Fonseca et al with their results also found to be statistically significant. 6 In terms of admission to NICU, similar results were seen in other two studies mentioned by Fonseca et al, and Romero et al, with their results also found to be statistically significant (p = 0.05 and p = 0.003 respectively).…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were seen in two other studies by Anjali et al, and Romero et al, with their results also found to be statistically significant (p = 0.044 and p = 0.003 respectively). 14,15 At gestational age between 33 to <35 weeks of gestation this comparison has been found to be statistically significant (p = 0.045) in the present study. Similar results were seen in other studies by Fonseca et al, Hassan et al, Anjali et al, and Romero et al, with their results also found to be statistically significant (p = 0.007, p = 0.016, p = 0.044 and p = 0.003 respectively).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations